2013
DOI: 10.1002/cyto.b.21076
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry is of limited utility in the early identification of “Double‐hit” B‐cell lymphomas

Abstract: Background: B-cell lymphomas with concurrent translocations of MYC and BCL2 or BCL6, also known as ''double-hit'' lymphomas (DHL), are rare malignancies characterized by aggressive clinical behavior and poor prognosis. Previous reports suggest that decreased CD20 and/or CD19 expression by flow cytometry is relatively common in DHL and may help to identify cases requiring additional cytogenetic analysis.Methods: We conducted a retrospective analysis of 26 cases of DHL, and compared their flow cytometric charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…DHL and triple-hit lymphomas could arise from follicular and DLBCL following the acquisition of MYC rearrangement in the molecular pathologic evolution of the disease (2). Seven-color flow cytometric immunophenotyping could be more accurate than four-color studies for DHL diagnosis (3). Controversy has arisen regarding the utility of flow cytometry for the diagnosis of DHL.…”
Section: Discussionsupporting
confidence: 89%
“…DHL and triple-hit lymphomas could arise from follicular and DLBCL following the acquisition of MYC rearrangement in the molecular pathologic evolution of the disease (2). Seven-color flow cytometric immunophenotyping could be more accurate than four-color studies for DHL diagnosis (3). Controversy has arisen regarding the utility of flow cytometry for the diagnosis of DHL.…”
Section: Discussionsupporting
confidence: 89%
“…Limiting dilution assay to quantify cytotoxic T-lymphocyte precursor frequencies and IL-2-producing T helper frequencies were performed as described (20). Lymphocyte subsets were monitored by flow cytometry as previously described (21). …”
Section: Methodsmentioning
confidence: 99%
“…14,20,47 Flow cytometric demonstration of dim CD20 and/or dim CD19 to help identify DHL has also been reported, but others find it to be of limited utility because most cases do not have these features. [48][49][50] But what about the role of MYC IHC? It has been reported that finding Ն70% MYCϩ cells had a sensitivity of 100% and specificity of 93% for a MYC break.…”
Section: What Are the Implications Associated Controversies And Ongmentioning
confidence: 99%